2021
DOI: 10.3390/ijms222011137
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Cancer: In Search for a Causal Link

Abstract: Insulin resistance (IR) is a condition which refers to individuals whose cells and tissues become insensitive to the peptide hormone, insulin. Over the recent years, a wealth of data has made it clear that a synergistic relationship exists between IR, type 2 diabetes mellitus, and cancer. Although the underlying mechanism(s) for this association remain unclear, it is well established that hyperinsulinemia, a hallmark of IR, may play a role in tumorigenesis. On the other hand, IR is strongly associated with vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 330 publications
(361 reference statements)
1
66
1
Order By: Relevance
“…Sixthly, increasing scholars begin to pay attention to the role of metabolism in the occurrence and development of cancer, and we also tried to explore the relationship between IR and cancer-related mortality. Although previous studies have shown that IR and metabolic syndrome were associated with higher risks of cancer and cancer-related death ( 55 , 56 ), our study failed to find a linear or non-linear relationship between METS-IR and cancer-related mortality, which may be due to the heterogeneity of the study population and the small sample size. Finally, there may be other residual confounding factors that have not been controlled, such as oxidative stress, inflammatory, thrombotic status, and genetic susceptibility.…”
Section: Study Limitationscontrasting
confidence: 93%
“…Sixthly, increasing scholars begin to pay attention to the role of metabolism in the occurrence and development of cancer, and we also tried to explore the relationship between IR and cancer-related mortality. Although previous studies have shown that IR and metabolic syndrome were associated with higher risks of cancer and cancer-related death ( 55 , 56 ), our study failed to find a linear or non-linear relationship between METS-IR and cancer-related mortality, which may be due to the heterogeneity of the study population and the small sample size. Finally, there may be other residual confounding factors that have not been controlled, such as oxidative stress, inflammatory, thrombotic status, and genetic susceptibility.…”
Section: Study Limitationscontrasting
confidence: 93%
“…Obese individuals often have impaired insulin sensitivity, which causes pancreatic beta-cells to promote insulin production, leading to hyperinsulinemia and insulin resistance (IR) [88]. Several studies support the hypothesis of a link between IR and increased risk of many cancers, including TC [89][90][91][92]. Insulin is not only a metabolic hormone but also a cell growth factor that can stimulate the mitogenic cascade by activating the MAPK and mTOR pathways.…”
Section: Insulin Resistance and Hyperinsulinemiamentioning
confidence: 99%
“…Inflammation was a key cause of the development and progression of many chronic diseases, including cancer ( 39 ). Moreover, inflammatory cytokines such as tumor necrosis factor (TNF)-a, induced by SFA, may influence insulin sensitivity ( 40 ), which favored the establishment of a pro-tumorigenic environment ( 41 ). Fatty acylation was another potential carcinogenic mechanism of SFA.…”
Section: Discussionmentioning
confidence: 99%